The Effectiveness of Giving Betel Leaves in Overcoming Flour Albus Teenagers - Ernik Anggraini; Priharyanti Wulandari (Global Health Science Group, 2020)
Flour albus is a vaginal condition when discharge or mucus resembles pus. Leucorrhoea is not always a disease because there is also normal Flour Albus In Indonesia, about 90% of women have the potential to experience Flour Albus Leucorrhoea experienced by adolescent women aged 15-24 years, which is around 31.8%. One of the non-pharmacological treatments for leucorrhoea is betel leaf. Betel leaf contains essential oils, phenyl propane, estragol, kavicol, hidroksikavicol, kavibetol, caryophyliene This study aims to determine the effectiveness of giving betel leaf stew in overcoming vaginal discharge in adolescents in Bambankerep Village, Kedungpani Subdistrict, Mijen District, Semarang City. The research used a descriptive method with a case approach to adolescents suffering from vaginal discharge from 26 July to 1 August 2020. The instrument used was a data observation sheet using assessment by interviewing. The targets are adolescents with betel leaf therapy given for 7 days, twice a day as much as 100 cc. Respondents before being given betel leaf decoction therapy often experienced vaginal discharge so that the respondents felt uncomfortable. After being given betel leaf decoction therapy, the vaginal discharge decreased. This study is proven to be effective in giving betel leaf stew to reduce vaginal discharge.